Development of padded bandana for takraw players - Muhammad 'Azri, Mohd Razi (2013)
This study focuses on the analysis of a headband which is called the bandana. Takraw player often used a bandana on the head just for covering their hair and to sweep sweat. Unfortunately, the bandana is much more unprotected compared to headband because it does not have a material that can absorb an impact from the ball thus can cause a severe injury after several times of heading. It is shown that the understanding of the head impact with this bandana wearing by players in a game is imminent to the biomechanics knowledge. The objective of this study is to identify the most suitable material of bandana and fabricate a bandana based on the result of the experiment that has been conducted. This study involved with 2 types of experiment, which the first experiment conducted on the force plate in order to find the most suitable material for bandana among the 3 types of test material. For the second experiment conducted on the skull prototype in order to compare the parameters between best material results from the previous experiment and a condition without using any test material. The expected result produces from the experiment is the value of material should be relatively closed to or higher or lower than the benchmark value according to each parameter. A material that satisfies each parameter of the experiment was proven as the best material for padded bandana for Takraw players.